Bio-priming with a consortium of Streptomyces araujoniae strains modulates defense response in chickpea against Fusarium wilt - Zeyad, Mohammad Tarique; Tiwari, Pushpendra; Ansari, Waquar Akhter; Kumar, Shiv Charan; Kumar, Murugan; Chakdar, Hillol; Srivastava, Alok Kumar; Singh, Udai B.; Saxena, Anil Kumar (Frontiers in Microbiology, 2022)
Wilt caused by Fusarium oxysporum f. sp. ciceris (Foc) is one of the major diseases of chickpea affecting the potential yield significantly. Productivity and biotic stress resilience are both improved by the association and interaction of Streptomyces spp. with crop plants. In the present study, we evaluated two Streptomyces araujoniae strains (TN11 and TN19) for controlling the wilt of chickpea individually and as a consortium. The response of Foc challenged chickpea to inoculation with S. araujoniae TN11 and TN19 individually and as a consortium was recorded in terms of changes in physio-biochemical and expression of genes coding superoxide dismutase (SOD), peroxidase, and catalase. Priming with a consortium of TN11 and TN19 reduced the disease severity by 50-58% when challenged with Foc. Consortium primed-challenged plants recorded lower shoot dry weight to fresh weight ratio and root dry weight to fresh weight ratio as compared to challenged non-primed plants. The pathogen-challenged consortium primed plants recorded the highest accumulation of proline and electrolyte leakage. Similarly, total chlorophyll and carotenoids were recorded highest in the consortium treatment. Expression of genes coding SOD, peroxidase, and catalase was up-regulated which corroborated with higher activities of SOD, peroxidase, and catalase in consortium primed-challenged plants as compared to the challenged non-primed plants. Ethyl acetate extracts of TN11 and TN19 inhibited the growth of fungal pathogens viz., Fusarium oxysporum f. sp. ciceris. Macrophomina phaseolina, F. udum, and Sclerotinia sclerotiarum by 54-73%. LC-MS analyses of the extracts showed the presence of a variety of antifungal compounds like erucamide and valinomycin in TN11 and valinomycin and dinactin in TN19. These findings suggest that the consortium of two strains of S. araujoniae (TN11 and TN19) can modulate defense response in chickpea against wilt and can be explored as a biocontrol strategy.